Psychosexual health 5 years after hysterectomy: population-based comparison with endometrial ablation for dysfunctional uterine bleeding. - McPherson, K; Herbert, A; Judge, A; Clarke, A; Bridgman, S; Maresh, M; Overton, C (2005)
BACKGROUND: We report a population-based comparison of psychosexual health 5 years after contrasting amounts of surgical treatments for heavy periods [dysfunctional uterine bleeding (DUB)]. Women's fears about sexual function after hysterectomy might not be unfounded. The psychosexual problems may return and/or develop with time. The removal of ovaries at the time of hysterectomy is associated with greater deterioration of self-reported sexual function. Surgical menopause significantly impairs sexual wellbeing. We failed to observe uniform beneficial effects of hormone replacement therapy (HRT) on reported psychosexual health. OBJECTIVE: To compare self-reported bothersome sexual function; loss of interest in sex, difficulty in becoming sexually excited and vaginal dryness 5 years after surgical management of DUB [transcervical endometrial resection/ablation (TCRE) or subtotal and total hysterectomy, with and without prophylactic bilateral oophorectomy (BO)]. DESIGN: Prospective cohort study up to 5 years post-surgery for DUB, TCRE or hysterectomy, with or without BO. SETTING: Over 400 NHS and private hospitals in England, Northern Ireland and Wales. COHORT: Of 11,325 women who responded to the 5-year questionnaire, over 9500 (84%) were valid cases, and over 8900 (94%) did complete the questions relating to psychosexual function. Most were between the ages of 39 and 45 years, married or cohabiting. MAIN OUTCOMES: Self-reported experience of bother, recorded as 'some', 'severe' and 'extreme', to questions on (1) libido loss, (2) difficulty with sexual arousal, and (3) vaginal dryness during the past 4 weeks, 5 years after surgery. RESULTS: Five years after surgery for DUB, the crude and adjusted prevalence of psychosexual problems was higher after hysterectomy than after TCRE. Amongst the women with concurrent BO, the age- and HRT-adjusted odds ratios for extreme psychosexual problems were increased by 80% (libido loss), 82% (difficult sex arousal) and 69% (vaginal dryness) compared with TCRE. CONCLUSIONS: Five years after hysterectomy more women reported having bothersome psychosexual function than did the women who had a less invasive operation. Hormone therapy, although related to surgical method, did not reduce this long-term detrimental effect. The odds were particularly high amongst women with concurrent BO. Women should be advised that they might be at higher risk of psychosexual problems following hysterectomy, compared with a less invasive procedure.